“Making family across borders”: Proximities and distances at the heart of the research process on the experiences of separation and reunification of transnational refugee families (Clinical Sociology Review, 2024)
This article takes a reflective look at the scientific approach at the heart of a doctoral thesis in social work aimed at studying the experiences of separation and reunification of members of transnational refugee families in Quebec/Canada. Through a "feminist memory work" it presents: 1) the problematic as well as the theoretical and methodological framework of the thesis; 2) a "situation" (Ahmed, 2024) that was decisive in the choice of doctoral research object; 3) an analysis mobilizing among other things the concept of intersectional praxis "in and outside" of one's social class and racialized group (Bilge and Hill Collins, 2023; hooks, 2018) in order to reflect on the ways of conducting a scientific process whose mission is to learn about the experience of others and to transform the sources of oppression that affect them.